Legal Analysis of the Fulfillment of the Rights of Disabled and Elderly Inmates at Class IIB Muntok Prison - Adrian, Achmad; Sukrisno, Wijayono Hadi (Dinasti Research, 2025)
This study examines the legal fulfillment of the rights of disabled and elderly inmates at Class IIB Muntok Prison. The research analyzes compliance with national and international legal standards governing the treatment of inmates with special needs. Employing a normative juridical approach, this study reviews existing regulations, policies, and their implementation within the prison system. Key findings indicate that while legal frameworks exist to protect the rights of disabled and elderly inmates, challenges persist in their practical application due to limited resources, lack of accessibility, and inadequate training for prison staff. The study highlights the need for enhanced infrastructure, specialized healthcare, and tailored rehabilitation programs to ensure equal treatment and protection of vulnerable inmates. Recommendations include policy revisions and capacity-building initiatives to bridge the gap between legal mandates and actual practice, promoting a more inclusive correctional environment aligned with human rights principles.